Mechanical properties of geopolymer concretes reinforced with waste steel fibers - Gailitis, R (2019)
The article presents the research that try to determinate the possibilities of utilization the waste came from used tires to create the composites based on geopolymer matrix. The tire is multicomponent construction. It mainly consists of elastomer (rubber), metal and textile fibres such called textile cord. A lot of components causes difficulties in the tire recycling process. The main aim of the research was determinate the possibilities of recycling the waste steel from used tires in geopolymer composites and develop the eco-friendly material for construction industry. The matrix based on fly ash from power station located in city named Skawina (Poland) and fine sand at a ratio of 1:1. The process of activation was made by 10M sodium hydroxide solution combined with the sodium silicate solution. In order to manufacture these composites the addition of 2% and 3.5% of waste steel fibres by mass was applied. Also specimen without steel fiber reinforcement were made to get reference specimens. The waste steel fibres came from recycling company from Argentina - 'Regomax'. The specimens were prepared according to the methodology described in the standard EN 12390-1. The research methods used were: microstructure research, tensile strength and compressive strength tests as well as analysis of breakthroughs.